Tapping the Sources of Self-Efficacy: Promoting Preservice Teachers' Sense of Efficacy for Instructing English Language Learners. Issue 3 (3rd July 2019) - Yough, Mike
Abstract: The primary objective of the current study was to examine the effects of an intervention to promote preservice teachers' sense of efficacy for teaching English language learners (ELLs). Participants were undergraduates enrolled in either a "non-intervention" or "intervention" section of an educational psychology course. Results revealed that those receiving the invention had a higher sense of efficacy for instructing ELL students than those who did not, but that participants in both groups had a higher sense of efficacy for students in general than for ELL students specifically.